2005
DOI: 10.1038/sj.ijo.0803073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2-month detraining on body composition and insulin sensitivity in young female dancers

Abstract: Objective: To investigate the effect of 2-month detraining on body composition and glucose tolerance for female collegiate dancers. Design: Longitudinal study of dancers who stopped their regular training for 2 months. Subjects: 16 female collegiate dancers (age: 19.770.11 year, body mass index (BMI): 20.770.56 kg/m 2 ). Measurements: BMI, waist-to-hip ratio (WHR), oral glucose tolerance test (OGTT), insulin response during OGTT, and blood lipids at baseline and after a 2-month detraining. Results: Glucose tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
8
0
4
Order By: Relevance
“…5,6 Other studies have reported an unmodified resting metabolic rate 7 and reduced insulin sensitivity. 8 We believe that the abrupt summer break from swimming training may lead to unfavorable changes in the anthropometric characteristics of the swimmers. Therefore, the aims of this study were to monitor the effects of summer break from swimming activity on anthropometric profile, body composition and somatotype of adolescent swimmers and to compare these changes to the less active adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Other studies have reported an unmodified resting metabolic rate 7 and reduced insulin sensitivity. 8 We believe that the abrupt summer break from swimming training may lead to unfavorable changes in the anthropometric characteristics of the swimmers. Therefore, the aims of this study were to monitor the effects of summer break from swimming activity on anthropometric profile, body composition and somatotype of adolescent swimmers and to compare these changes to the less active adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…El ligerísimo aumento no significativo de la MME podría ser debido a la asociación del ACT con la masa muscular y sus componentes tanto extra como intracelular que se observa tras el DT, habiéndose descrito modelos de regresión múltiple de los cambios del peso corporal a través de cambios del AEC que explicarían un 55% de la varianza en el cambio del peso corporal (13). La migración del vector de impedancia eléctrica (19,26) indica una doble dirección: hacia abajo y hacia la izquierda, lo cual denota un aumento del líquido corporal o rehidratación y un aumento de la masa grasa, que está en consonancia con los resultados encontrados en nuestras pruebas antropométricas y con la literatura (5). El análisis del vector de impedancia es considerado una buena herramienta para detectar cambios en la hidratación ya que no depende del peso del sujeto y permite la visualización gráfica de cambios tanto de la hidratación como de la masa celular activa (19,26,33,34).…”
Section: Discussionunclassified
“…Estas modificaciones pueden circunscribirse solamente a ciertos marcadores de adiposidad regional central como el perímetro abdominal o el índice cintura-cadera, sin afectar al índice de masa corporal (IMC) (5). Por todo ello es importante el control de la CC, pues tras cinco semanas de desentrenamiento se ha observado un aumento de la masa grasa y del perímetro de la cintura y estos cambios estuvieron asociados a disminuciones del consumo máximo de oxígeno y la tasa metabólica de reposo en jóvenes nadadores (6).…”
Section: Introductionunclassified
“…Já em atletas pode não ser observado aumento do peso corporal no destreinamento a curto prazo, no entanto, em alguns casos, pode haver aumento da circunferência da cintura (LIU T. C. et al, 2008). Quando o período de destreinamento é estendido para além de 4 semanas pode ser observado além do aumento da circunferência da cintura (CHEN et al, 2006), aumento do peso e do índice de massa corporal (IMC), mudanças na composição corporal (aumento da massa adiposa e redução da massa magra), no perfil lipídico (aumento do LDL colesterol e redução do HDL colesterol), na sensibilidade à insulina, na captação de glicose e na capacidade aeróbica em indivíduos sedentários ou atletas (LIU et al, 2008;MITSUHASHI et al, 2011;PETIBOIS et al, 2004).…”
Section: Destreinamento Físicounclassified